A comercialização de uvas finas na região de Jales – SP - Almeida Lima Costa, Silvia Maria [UNESP]; Lacerda Gomes, Marcos Roberto; Anselmo Tarsitano, Maria Aparecida [UNESP] (Soc Brasileira Fruticultura, 2008)
The production of fine grapes stands out among the most important economical activities in the Northwest region of the State of São Paulo, Brazil. However, this area's farmers commonly point out problems referring to the commercialization of the fruit as one of the most important obstacles interposed to the development of the regional horticulture. This work analyzes the transactions between producers and the agents of the fruit commercialization, arguing about the actual governance structures and the reasons which explain the producers exposition to opportunist behaviors associated to the delivers. It is concluded that producers who develop more specialized productive systems and offer better quality of fruits are attended by intermediary agents also specialized, and therefore they are less exposed to opportunist behaviors. In these cases the relationship between the agents becomes more effective and systematic, and the governance structures transits from market coordination through hybrid forms.
Comercialization of fine grapes in the region of Jales, State of São Paulo
Keywords: grape; transaction economics cost; fruit commercialization